Seaweed Diversity at Muluk Beach, Sengkol Village, Pujut Sub-District, Central Lombok Regency, Nusa Tenggara Barat - Nunik Cokrowati; Nur Yatin; Jayusri Jayusri; Muhammad Jum’at; Salnida Yuniarti Lumbessy; Wiyat Zahroh Sepia Utami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Seaweed can produce compounds that have diverse biological activities, including antioxidants. These compounds can be used in food, food sources, and medicines. This study aimed to analyze the types of seaweed that grow wild in the waters of Muluk Beach. The research was conducted at Muluk Beach, Sengkol Village, Pujut District, Central Lombok Regency. The research methods used in this study were survey methods and laboratory experiments. The results explained that the type of wild seaweed that grows in the waters of Muluk Beach is Padina sp, Gracilaria coronopifolia, Sargassum cristaefolium, Gracilaria sp, Caulerpa taxifolia, C. taxifolia, Ulva intestinalis, Halimeda opuntia, Ulva sp, Codium, H.tuna, G.salicornia, G.verrucosa, and Acanthopora. The type with the highest antioxidant content is Padina sp, which is 81,31% and has 14,39 mg/L chlorophyll-a levels. The species with the lowest antioxidant content was H.opuntia at 1,79% and chlorophyll at 8,83 mg/L.